Technology readiness and usability of office automation system in suburban areas - Dwi Yuniarto; A’ang Subiyakto; Aedah Abd. Rahman (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Readiness and usability issues are important attributes of an information system (IS) success. Currently, IS studies that have been assessing the issues in suburban areas are still limited. The purpose of this study was to measure the above-mentioned phenomena by combining the readiness and usability models. The proposed model consisted out 10 constructs with 25 indicators. The four constructs were from the readiness model and the six ones were the usability model. The 89 samples were collected using an online survey based on purposive random sampling. Partial least squares structural equation modeling (PLS-SEM) method with SmartPLS 3.2.8 was used for analyzing the data. The findings may have contributed to the IS research field, in terms of the readiness and usability issues on the IS use in a suburban area in Indonesia.